2017
DOI: 10.1371/journal.pone.0181497
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint effects of moderate alcohol consumption and smoking on the risks of non-alcoholic fatty liver disease in elderly Chinese men

Abstract: BackgroundWhether cigarette smoking and moderate drinking are associated with non-alcoholic fatty liver disease (NAFLD)has not been fully described. This study investigated the separate and joint effects of smoking and moderate drinking on Chinese men with NAFLD.MethodsAcross-sectional assay from DFTJ Cohort study was performed with a size of 9432 elderly Chinese men excluding excessive alcohol consumption (<210g/week). Fatty liver was diagnosed by standardized ultrasonographic inspection. The odds ratio (OR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
(45 reference statements)
2
26
0
Order By: Relevance
“…Smoking status was categorized into nonsmokers, former smokers and current smokers on the basis of self-reported amount and length of cigarette smoking. Current smokers were those who smoked regularly at least once a day or more for more than half a year, and former smokers were those who used to smoke but stopped smoking at least half a year prior to the study [38]. Alcohol drinking status was classified into non-drinkers, former drinkers and current drinkers based on the self-reported amount and duration of alcoholic beverages.…”
Section: Other Covariatesmentioning
confidence: 99%
“…Smoking status was categorized into nonsmokers, former smokers and current smokers on the basis of self-reported amount and length of cigarette smoking. Current smokers were those who smoked regularly at least once a day or more for more than half a year, and former smokers were those who used to smoke but stopped smoking at least half a year prior to the study [38]. Alcohol drinking status was classified into non-drinkers, former drinkers and current drinkers based on the self-reported amount and duration of alcoholic beverages.…”
Section: Other Covariatesmentioning
confidence: 99%
“…15 In addition, a recent cross-sectional study showed that current smokers had a higher risk of NAFLD than nonsmokers. 17 Contrary to these studies, some other studies have been unable to demonstrate an association between smoking and NAFLD. Chavez-Tapia et al 13 showed that the risk of NAFLD was not different between current smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 84%
“…A population‐based study from China also reported that passive smoking (OR, 1.25; 95% CI, 1.05‐1.50) and active heavy smoking (OR, 2.29; 95% CI, 1.30‐4.03) significantly increased the risk of NAFLD . In addition, a recent cross‐sectional study showed that current smokers had a higher risk of NAFLD than nonsmokers . Contrary to these studies, some other studies have been unable to demonstrate an association between smoking and NAFLD.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations